Performance of Islamic Boarding Schools in developing the beef cattle agribusiness partnership network as a community empowerment institution in Central Java - Harjanto, J. T.; Prasetyo, E.; Santoso, S. I.; Rianto, E. (Diponegoro University, 2019)
A study had been conducted to evaluate the performance of Islamic Boarding Schools (IBS) in developing the beef cattle agribusiness partnerships network in Central Java. This study involved 24 IBS with each IBS selected two respondents, namely one from internal (santri) and one from external (farmer community). Sample determination uses purposive sampling method. This study uses Gap Analysis by determining the Customer Satisfaction Index (CSI) value. Primary data were collected through direct observation and interviews with respondents. Secondary data was obtained from relevant government institutions. The results showed that the beef cattle agribusiness partnership network that was developed by IBS still did not satisfy for santries and farmer communities (CSI.s.total : 30.73% and CSI.f.total : 47.05%). It was concluded that farmer communities were very enthusiastic about establishing the beef cattle agribusiness partnerships with IBS; the santries needed additional livestock curriculums; IBS needed training and assistance from the other parties (government, private sector, etc.) in order to improve the ability to raise beef cattle and the ability to train, instruct and plan the beef cattle farming development in surrounding area. Increasing the ability of IBS automatically can increase the effectiveness of IBS role as an empowerment institution for surrounding community.